The E. coli CsgB nucleator of curli assembles to β-sheet oligomers that alter the CsgA fibrillization mechanism - Shu, Qin (National Academy of Sciences, 2012)
Curli are extracellular proteinaceous functional amyloid aggregates produced by Escherichia coli, Salmonella spp., and other enteric bacteria. Curli mediate host cell adhesion and invasion and play a critical role in biofilm formation. Curli filaments consist of CsgA, the major subunit, and CsgB, the minor subunit. In vitro, purified CsgA and CsgB exhibit intrinsically disordered properties, and both are capable of forming amyloid fibers similar in morphology to those formed in vivo. However, in vivo, CsgA alone cannot form curli fibers, and CsgB is required for filament growth. Thus, we studied the aggregation of CsgA and CsgB both alone and together in vitro to investigate the different roles of CsgA and CsgB in curli formation. We found that though CsgA and CsgB individually are able to self-associate to form aggregates/fibrils, they do so using different mechanisms and with different kinetic behavior. CsgB rapidly forms structured oligomers, whereas CsgA aggregation is slower and appears to proceed through large amorphous aggregates before forming filaments. Substoichiometric concentrations of CsgB induce a change in the mechanism of CsgA aggregation from that of forming amorphous aggregates to that of structured intermediates similar to those of CsgB alone. Oligomeric CsgB accelerated the aggregation of CsgA, in contrast to monomeric CsgB, which had no effect. The structured β-strand oligomers formed by CsgB serve as nucleators for CsgA aggregation. These results provide insights into the formation of curli in vivo, especially the nucleator function of CsgB.